Heterogeneity in the Continuity and Change of Early and Adult Risk Factor Profiles of Incarcerated Individuals: A Latent Transition Analysis - Fox, Bryanna (Youth violence and juvenile justice, 2021)
Considerable research has examined risk factors for offending, but far less is known on the constellations of co-occurring risk factors, such as adverse childhood experiences and low self-control, and the overall continuity in risk between childhood/adolescence and adulthood. Using data on 735 adults incarcerated in a county jail in Florida, this study examines the latent heterogeneity in risk profiles using risk factors prominent in early years and adulthood, and whether risk profile severity changes across the early and adult risk models.Latent Class Analyses revealed three risk profiles (low, medium, high) in both the early and adulthood risk factor models. Transition probabilities indicate continuity in high and low risk in the early and adult models, while escalation was found for those in the low and medium early risk profiles. These findings demonstrate the importance of identifying and addressing risk factors at an early age to disrupt continuity and escalation in risk over the life-course.